Diseño, planificación e implementación de estrategias en la industria manufacturera industrial para el diseño de productos. (2011)
In a industrial design company, each department of this greatly influences when presenting to the customer a finished product design, which was required for him. That´s why the way you perform a project most contain strategies that will enable the company to stand out from the moment the best way to implement them.